Prevalence of workplace smoking bans in Victoria - Ron Borland; Maxine Morand; Robyn Mullins (Elsevier, 1997)
Abstract: Restrictions on smoking in the Victorian workplace have been measured since 1988. This paper investigates whether the trend of increasing prevalence of total bans found between 1988 and 1992 has continued. Estimates are based on workers' reports of the restrictions on smoking that apply at their workplaces. For indoor workers a total ban on smoking restrictions in the workplace has increased from 58% in 1992 to 66% in 1995. White collar workers continue to enjoy a higher rate of protection than blue collar workers. Factories, warehouses, hotels and restaurants are the worksites least likely to have restrictions. Bans result in considerable exiled smoking: half the smokers reported going out to smoke during working hours on their last work day. (Aust N Z J Public Health 1997; 21: 694-8)